2016
DOI: 10.1021/acs.est.5b03410
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Matter in Its Native State: Unravelling the Most Complex Biomaterial on Earth

Abstract: Since the isolation of soil organic matter in 1786, tens of thousands of publications have searched for its structure. Nuclear magnetic resonance (NMR) spectroscopy has played a critical role in defining soil organic matter but traditional approaches remove key information such as the distribution of components at the soil-water interface and conformational information. Here a novel form of NMR with capabilities to study all physical phases termed Comprehensive Multiphase NMR, is applied to analyze soil in its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 54 publications
4
75
0
3
Order By: Relevance
“…In the contact zone of this model, proteins are proposed to sorb to the surface of phyllosilicate minerals through polar interactions, including electrostatic, cation bridging or ligand exchange associations, as well as more non-polar interactions such as hydrophobic and van der Waals bonding [51,52]. In addition, Masoom et al [28] reported that protein components of soil OM were not visible when a soil was swollen in D 2 O, but could be observed using DMSO-d 6 , a solvent which disrupts hydrogen bonding and hydrophobic interactions and penetrates beneath the outermost layers of OM [29]. This suggested that proteins are buried deeper within the soil OM microstructure and may be sorbed to the mineral surface as observed in the present study.…”
Section: Sorption Of Specific Dom Components To Kaolinitementioning
confidence: 99%
See 3 more Smart Citations
“…In the contact zone of this model, proteins are proposed to sorb to the surface of phyllosilicate minerals through polar interactions, including electrostatic, cation bridging or ligand exchange associations, as well as more non-polar interactions such as hydrophobic and van der Waals bonding [51,52]. In addition, Masoom et al [28] reported that protein components of soil OM were not visible when a soil was swollen in D 2 O, but could be observed using DMSO-d 6 , a solvent which disrupts hydrogen bonding and hydrophobic interactions and penetrates beneath the outermost layers of OM [29]. This suggested that proteins are buried deeper within the soil OM microstructure and may be sorbed to the mineral surface as observed in the present study.…”
Section: Sorption Of Specific Dom Components To Kaolinitementioning
confidence: 99%
“…Furthermore, components present in the outermost layers of OM sorbed to the organo-clay complexes were characterized at selected intervals using high resolution-magic angle spinning (HR-MAS) NMR. This NMR technique permits the analysis of OM components in solid, solution and gel phases of a sample using a single NMR probe, and has been used previously to study soil OM chemistry at interfaces [14,15,28,37]. We hypothesize that the quantity and composition of OM sorbed to the initial uncoated clay mineral surfaces will be controlled primarily by mineral properties such as SSA and CEC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In many ways, CMP NMR can be thought of as changing NMR technology to match natural samples, rather than changing the sample to match a specific NMR technique. CMP NMR has permitted the study of structural interactions and processes in unaltered heterogeneous samples, including soil, swelling of rubber by biofuels, intact plants, and to follow biological processes (seed growth) …”
Section: Introductionmentioning
confidence: 99%